Effect of photocatalyst dosage and air loading in photocatalytic degradation of metamifop. Issue 1 (August 2021) - Nik Yusoff, N R; Lim, P W; Azmi, N A B; Yusoff, M; Muhammad, M
Abstract: Excessive used of agrochemical product such as metamifop herbicide, besides having high crop yield production, it has resulted in runoff which later affected groundwater and give negative impact on the environment. Photocatalytic degradation is one of the Advanced Oxidation Process where it creates hydroxyl radicals (·OH) in the presence of UV light. Performance of TiO2 /Al2 O3 /carbon nanotube (CNT) (10 mg and 20 mg) which was produced through a hydrothermal process was applied to degrading 5 ppm and 10 ppm of metamifop. The performance of TiO2 /Al2 O3 /CNT to degrade metamifop was evaluated statistically via a two-way analysis of variance (ANOVA) followed by a post-hoc Turkey's test. The average performance of photocatalytic degradation gave a significant result at confident level of 0.05 hence the null hypothesis (Ho ) was rejected. The best performance was occurred in degrading 5 ppm of metamifop using 20 mg of TiO2 /Al2 O3 /CNT photocatalyst in the presence of air (2L/min) which resulted in 95.26% of percentage degradation. The addition of air assisted the photocatalytic degradation process from 84.54% to 92.44% and 83.62% to 91.47% when 10 mg of photocatalyst was used to degrade 5 ppm and 10 ppm of metamifop, respectively. When 20 mg of TiO2 /Al2 O3 /CNT photocatalyst was applied in degrading 5 ppm and 10 ppm metamifop, the percentage degradation increased from 86.94% to 95.26% and 85.88% to 94.62%, respectively when photocatalytic degradation was conducted in the absence of air to the presence of air. The inferential results show a significant difference in average performance of TiO2 /Al2 O3 /CNT photocatalyst and concentration of metamifop solution. However, there is no interaction effect between dosages of photocatalyst used with consumption of air in degrading metamifop. The study also proved that the produced photocatalyst was performed very well and suitable to be used in degrading metamifop herbicide.